Pneumocystis jirovecii infection of the external auditory canal - Catherine Mary Samuel; Sairita Maistry; Estie Meyer; Andrew Whitelaw (Southern African Journal of HIV Medicine, 2010)
Pneumocystis jirovecii is well known to cause interstitial plasma cell pneumonia in immunocompromised patients. It has been implicated as a rare cause of infections in other anatomical sites. We report a rare case of P. jirovecii infection of the external auditory canal. This was the first manifestation of a previously unknown HIV infection.